033 Extracranial-tumor cerebri. Issue 9 (12th August 2022) - Heller, Simon; Obholzer, Rupert; Wong, Sui
Abstract : Pseudotumor Cerebri Syndrome (PTCS) is the condition of raised intracranial pressure without a focal intracranial lesion. We present a patient with PTCS caused by an extracranial paraganglioma obstruct- ing his right internal jugular vein. This affected his intracranial venous drainage from his dominant right sided venous drainage; his left transverse and sigmoid sinus were hypoplastic. He experienced sympto- matic relief from acetazolamide, a temporising lumbar puncture and significant improvement following debulking surgery of the paraganglioma. CSF dynamics is more than the classical model of production in the choroid plexus and drainage through the arachnoid granulations. Increasingly we understand the role of nasal lymphatics via the cribriform plate and dural lymphatics via the glymphatic system. However, drainage via the arachnoid granulations and dural venous sinuses is still crucial. Papilloedema has a complex aetiology. Axonal transport stasis and pial-septal blood supply disruption secondary to raised ICP only tell part of the story. There is not free flow between the intracranial CSF and subarachnoid space of the optic nerve; raised ICP likely leads to compartmentalisation of the CSF around the optic nerve. Subsequent aggregation of a toxic milieu may contribute to optic disc oedema. Timely management of intracranial pressure is critical to preserve visual function.